A novel radar-based system for underground mine wall stability monitoring - Cecchetti, M.; Rossi, M.; Coppi, F.; Bicci, A.; Coli, N.; Boldrini, N.; Preston, C. (UMT 2017: Proceedings of the First International Conference on Underground Mining Technology, 2017)
Ground collapse is a serious issue for underground mining, and currently there is a lack of remote sensing monitoring systems to perform real-time deformation monitoring. Extensometers can be used in several situations; however, this instrumentation obliges the user to work close to unstable areas, thus a remote monitoring system would offer noticeably improved safety conditions. IDS GeoRadar, a provider of radar technology for slope monitoring in surface mining, recently developed an interferometric radar system for underground operations to monitor ground fall precursors and provide early warning in order to evacuate people and machinery at risk. This radar system is able to monitor slow deformations to produce preliminary risk assessment on potentially exposed instabilities in underground areas. The new radar system is able to provide sub-millimetre displacement accuracy at a spatial resolution of tens of centimetres, with updated displacement information every 30 seconds. In this paper, the system is described, along with performance test results and assessment of monitoring performances in real scenarios.